Effects of the Crustal Magnetic Fields and Changes in the IMF Orientation on the Magnetosphere of Mars: MAVEN Observations and LatHyS Results. Issue 7 (4th July 2018) - Romanelli, N.; Modolo, R.; Leblanc, F.; Chaufray, J‐Y.; Hess, S.; Brain, D.; Connerney, J.; Halekas, J.; Mcfadden, J.; Jakosky, B.
Abstract: The Mars Atmosphere and Volatile EvolutioN Mission (MAVEN) is currently probing the complex Martian environment. Although main structures arising from the interaction between the solar wind (SW) and the induced magnetosphere of Mars can be described using a steady state picture, time‐dependent physical processes modify the response of this obstacle. These processes result from temporal variabilities in the internal and/or external electromagnetic fields and plasma properties. Indeed, the crustal magnetic fields (CF) rotation constantly modifies the intrinsic magnetic field topology relative to the SW. Moreover, the magnetosphere's state is also modified by changes in the interplanetary magnetic field (IMF). In this work we analyze MAVEN magnetic field and plasma measurements obtained on 23 December 2014, between 06:00 UT and 14:15 UT. These measurements suggest that the external conditions remained approximately constant when MAVEN was inside the magnetosphere during the first orbit. In contrast, MAVEN observed changes in the IMF orientation before visiting the magnetosphere during the second orbit. To investigate the response of the Martian plasma environment to the CF rotation and IMF variability, we also perform hybrid simulations, using MAVEN observations to set SW external conditions. Simulation results are compared with the MAVEN measurements and show good agreement. Associated recovery timescales of different magnetospheric regions are found to range between ∼ 10 s and ∼ 10 min. Finally, we do not observe large variability in the total planetary H + and O + escape rates at different times during this event, although a correlation between the latter and the CF location is identified. Key Points: We study the responses of the Martian magnetosphere to variability in the IMF orientation, including crustal magnetic field effects Estimated recovery timescales of different magnetospheric regions range between ∼10 s and ∼10 min Computed H + and O + planetary ion loss rates do not show strong changes with the variability in the IMF orientation